PENGEMBANGAN PROFESIONALITAS GURU DALAM PEMANFAATAN LITERASI MULTIMODAL PADA PEMBELAJARAN - Dewi, Dian Novita; Inayati, Dian; Adi, Sugeng Susilo; Iswahyuni, Iswahyuni; Gozali, Agus; Bagus Umam, Muhammad; Sholikhah, Mar'atus; Tri Mulya Ningrum, Safrina; Eza Saputra, Bima (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Developing teacher competency is an essential thing that must be done both from internal and external encouragement. To contribute to the field of education, the community service team of English Language Education Study Program, Faculty of Cultural Studies, Universitas Brawijaya held teacher professional development training in the use of multimodal literacy in learning at SMP Negeri 27 Surabaya. The selection of the school was made in accordance with the collaboration agreement that both sides had drafted. The method used was a workshop held in 2 days with stages (1) Needs analysis, (2) First training; speakers' material delivery, (3) Second training; application usage practice, and (4) Evaluation; product creation by participants and contested. This activity provides a positive impact on teacher skills in preparing and carrying out lessons utilizing multimodal-based media in order to meet the needs of diverse learning styles of students and increase students' enthusiasm for learning.